The study of METTL3 and METTL14 expressions in childhood ETV6/RUNX1‐positive acute lymphoblastic leukemia. Issue 10 (20th August 2019) - Sun, Congcong; Chang, Lixian; Liu, Chao; Chen, Xiaoyan; Zhu, Xiaofan
Abstract: Background: This study was aimed to explore the METTL3 and METTL14 expressions in children with ETV6/RUNX1(E/R) ‐positive acute lymphoblastic leukemia (ALL) and investigate the relation between the METTL3 and METTL14 expressions with clinical features. Methods: Thirty‐seven newly diagnosed E/R ‐positive ALL children and six controls were included in this study. Real‐time quantitative polymerase chain reaction (RT‐PCR) was used to detect the mRNA expression level of METTL3 and METTL14 . Results: Among the 37 cases, 51.35% ( n  = 19) were boys and 48.65% ( n  = 18) were girls and the median age was 4.72 (1.72–11.99) years. Among the six controls, 50% ( n  = 3) were boys and 50% ( n  = 3) were girls and the median age was 5.24 (1.53–13.17) years. The expression level of METTL3 and METTL14 in E/R ‐positive ALL patients were lower than in controls ( p  < .05). Although failed to achieve statistical significance, the expression level of METTL3 and METTL14 in relapse patients were lower than nonrelapse patients ( p  = .171, p  = .150, respectively). Conclusion: The reduced levels of METTL3 and METTL14 suggest a possible role in the pathogenesis and course of E/R ‐positive ALL. METTL3 and METTL14 may become new prognostic factors, and rationalize specific treatment intensification in possible E/R ‐positive relapse patients. Abstract : METTL3 and METTL14 expressions were much lower in E/R ‐positive ALL patients than in controls and much lower in relapse patients than in nonrelapse patients. Thus, METTL3 and METTL14 may play important roles in the pathogenesis and relapse mechanism of pediatric E/R ‐positive ALL patients.